Fenomena Self-Alienation: Pengalaman Mahasiswa Perantauan dalam Mengelola Konflik Nilai dan Kehilangan Diri Otentik di Yogyakarta - Dewi Setyowati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Higher education often marks an important stage in which individuals migrate to pursue independence and prepare for their future careers. However, relocating to a new environment, particularly Yogyakarta as a multicultural city known as "Mini Indonesia," presents complex adaptation challenges. Migrant students not only encounter cultural differences but also engage in identity negotiation with local values, such as the unggah-ungguh norms, which may trigger value conflicts and experiences of self-alienation. This study aims to identify the forms of authentic self-loss, analyze how students interpret the phenomenon of self-alienation resulting from value conflicts, and explore the strategies they employ to manage and overcome such experiences. The research adopts an experiential qualitative approach using phenomenological methods to explore participants' subjective experiences in depth. It is grounded in the constructivist paradigm. Participants are selected through purposive sampling, consisting of active students in Yogyakarta who come from other regions and experience self-alienation or value conflicts during their adaptation process. Data are collected through semi-structured in-depth interviews and field notes and are analyzed thematically. The findings are expected to contribute to the development of personality and clinical psychology, particularly regarding the construction of self-alienation within the context of cultural transition, while also providing a foundation for developing psychological interventions for migrant students.